2022
DOI: 10.1186/s12890-021-01810-1
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone, venous thromboembolism, and association with heparin to 30 days in hospital survival in severe Covid-19 pneumonia

Abstract: Background Mortality in severe COVID-19 pneumonia is associated with thrombo-inflammation. Corticosteroids are given to attenuate the inflammation, but they are associated with thrombosis. The aims of this study were to determine the risk of venous thromboembolism between no methylprednisolone and methylprednisolone (dose versus duration) and to evaluate any synergistic dose-dependent association of heparin and methylprednisolone to 30 days in hospital survival. M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In contrast, Ronaldo and colleagues found an increase in VTE in individuals on steroids in their study. [25] The limitations of our study as a retrospective observational design are evident. We only looked at VTE and not COVID-19 related arterial thrombotic events such as myocardial infarctions or strokes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, Ronaldo and colleagues found an increase in VTE in individuals on steroids in their study. [25] The limitations of our study as a retrospective observational design are evident. We only looked at VTE and not COVID-19 related arterial thrombotic events such as myocardial infarctions or strokes.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, Ronaldo and colleagues found an increase in VTE in individuals on steroids in their study. [25]…”
Section: Discussionmentioning
confidence: 99%
“…Chronicity of corticosteroids is also associated with elevated levels of procoagulant factors. (22,35) Cushing's syndrome is a disease of excess endogenous glucocorticoids and it's associated with elevated levels of Factor VIII, Factor IX, and von Willebrand Factor (vWF). (36, 37) One in-vitro study suggested that exogenous corticosteroids increase synthesis of vWF and plasminogen-activator-1 (PAI-1).…”
Section: Discussionmentioning
confidence: 99%